The Effect Of Dictogloss Technique On Improving Students Writing Skill Of Descriptive Text At The Tenth Grade Students Of SMK Muhammadiyah Kudus - Nur Syafiq, Ahmad; Rahmawati, Amalia; Anwari, Anawari; ktaviana, Tyas O (Prosiding University Research Colloquium, 2021)
The aim of this study is to examine the effect of dictogloss technique on improving the writing ability of students on descriptive text at tenth grade students of SMK Muhammadiyah Kudus in the academic year of 2019/2020. This study was classroom action research using model of Kemmis dan McTaggart containing reconnaissance, planning, action dan observation and reflextion conducted in two cycles. The total samples of this study were all students of tenth grade of SMK Muhammadiyah Kudus consisting of 70 students. Later on, the data were collected through observation, interview and tests using interview guidlines, observation sheet and English writing rubric and then analyzed using descriptive analysis. This study showed that the use of dictogloss technique was able to improve writing skill of descriptive text for students. It can be seen from the different means from pre test and post test in the way that mean score of pre test was 8, in the cycle one was 9.5, in the cycle two was 11.63, and in the post test was 14,5. Furthermore, based on the application of its technique the students were able to generate their idea to produce well organized descriptive texts. They were also able to use the appropiate vocabulary, grammar, punctuation, spelling and capitalization in the writing. During the teaching and learning process they also showed positive responses towards the lesson, enthusiastically joined the teaching and learning activities and did the task well.